1995
DOI: 10.1002/ijc.2910630615
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of prostate‐cancer metastasis in vivo by a novel synthetic inhibitor of urokinase‐type plasminogen activator (uPA)

Abstract: Urokinase-type plasminogen activator (uPA) is a serine protease associated with tissue remodeling, cellular invasiveness, matrix degradation and tumor growth. Over-expression of uPA by the rat prostate-cancer cell line Dunning R3227, Mat LyLu, results in increased tumor metastasis to several non-skeletal and skeletal sites. Histological examination of these skeletal lesions has shown them to be primarily osteoblastic. In the present study we examined the capacity of a selective inhibitor of uPA enzymatic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(61 citation statements)
references
References 17 publications
1
59
0
1
Order By: Relevance
“…uPA-R is the best known modulator of uPA activation and it is expressed both by invasive PCa cells and normal osteoblasts (Rabbani et al 1994). The basic importance of the uPA/uPA-R system in the determination of PCa bone metastases has been clearly demonstrated in experimental animal models by the use uPA and uPA-R inhibitors (Rabbani et al 1995, Margheri et al 2005. Recently, some authors have suggested an important correlation between the function of the uPA/uPA-R system and EGF-R activation.…”
Section: Introductionmentioning
confidence: 99%
“…uPA-R is the best known modulator of uPA activation and it is expressed both by invasive PCa cells and normal osteoblasts (Rabbani et al 1994). The basic importance of the uPA/uPA-R system in the determination of PCa bone metastases has been clearly demonstrated in experimental animal models by the use uPA and uPA-R inhibitors (Rabbani et al 1995, Margheri et al 2005. Recently, some authors have suggested an important correlation between the function of the uPA/uPA-R system and EGF-R activation.…”
Section: Introductionmentioning
confidence: 99%
“…As the third drug, we have used an inhibitor of a serine proteinase, the urokinase inhibitor B428 (12). Like the MMPIs, B428 has shown some antitumor efficacy in preclinical models (13,14). However, clear indications that any of these drugs do indeed inhibit their target proteinases when administered systemically have not previously been presented.…”
Section: Introductionmentioning
confidence: 99%
“…The direct causal relationship between Plg activator expression and tumor progression was furthermore demonstrated in a number of studies using the chick chorio-allantoic membrane metastasis model, and the mouse spontaneous and experimental metastasis models. These studies have employed a variety of strategies to inhibit Plg activator function including antisense RNA techniques (Kook et al, 1994;Yu and Schultz, 1990), anti-catalytic Plg activator antibodies (Hearing et al, 1988;Kobayashi et al, 1994b;Ossowski, 1988;Ossowski and Reich, 1983), natural and synthetic Plg activator inhibitors or uPAR antagonists (Crowley et al, 1993;Kobayashi et al, 1994a;Min et al, 1996;Mueller et al, 1995;Rabbani et al, 1995), and, lately, also genetically engineered mice with targeted deficiencies in components of the PA system (Bugge et al, 1997(Bugge et al, , 1998Sabapathy et al, 1997;Shapiro et al, 1996). Collectively, these studies have firmly established the PA system as an important contributor to tumor progression.…”
Section: Introductionmentioning
confidence: 99%